Giant Dumbbell-Shaped Intra- and Extracranial Nerve Schwannoma in a Child Presenting with Glossopharyngeal Neuralgia Syncope Syndrome: A Case Report and Review of the Literature - Sarikaya-Seiwert, Sevgi; Klenzner, Thomas; Schipper, Jörg; Steiger, Hans-Jakob; Haenggi, Daniel (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Lower cranial nerve schwannomas are benign tumors of the neurolemmocytes of the cranial nerves. Among children, cranial nerve schwannomas are extremely rare and are predominantly associated with neurofibromatosis (NF) type 2. The purpose of the current case report is to describe a unique giant extra- and intracranial foramen jugular schwannoma in a young boy with lower cranial nerve deficits and glossopharyngeal neuralgia syncope syndrome and to review the pertinent literature. In the current case report, we illustrate the course of disease in a 14-year-old boy with a 4-month history of recurrent syncope and a big bulge on the left side of his neck. Audiometry showed deafness of the left ear. Magnetic resonance imaging (MRI) demonstrated a giant unilateral dumbbell-shaped intra- and extracranial foramen jugular schwannoma with a volume of 156 cm3 causing severe brain stem compression and obstructive hydrocephalus. The tumor was removed completely in a two-step surgery. The tumor was confirmed during surgery to originate from the glossopharyngeal nerve. The histological examination revealed the characteristic features of a schwannoma. The MRI 3 months after the second surgery confirmed complete tumor removal. The genetic examination for NF was negative. Review of literature showed that dumbbell-shaped lower cranial nerve schwannomas in the childhood population are rare.
Keywords: jugular foramen schwannoma; childhood; neurinoma; NF2; surgical tumor resection